Arsenic Species Analysis at Trace Level by High Performance Liquid Chromatography with Inductively Coupled Plasma Mass Spectrometry - Hou, Hongfang (Int J Anal Chem, 2019)
A sensitive and accurate simultaneous continuous analysis for six arsenic species including arsenobetaine (AsB), arsenocholine (AsC), monomethylarsonic acid (MMA), dimethylarsinic acid (DMA), arsenite (As(III)), and arsenate (As(V)) has been developed by high performance liquid chromatography with inductively coupled plasma mass spectrometry (HPLC-ICP-MS). An anion-exchange column of Hamilton PRP-X100 (Switzerland) was applied for separation of the six arsenic species with gradient elution of 1.25 mmol/L Na(2)HPO(4) and 11.0 mmol/L KH(2)PO(4) as the mobile phase A and 2.5 mmol/L Na(2)HPO(4) and 22.0 mmol/L KH(2)PO(4) as the mobile phase B. The linearity ranges for AsB, AsC, MMA, DMA, As(III), and As(V) were between 0.5 and 50.0 μg/L, and the detection limits of the six arsenic species were all within 0.01–0.35 ng/L. The relative standard deviations (RSDs) were within 2.26–3.68% and the recovery rates of samples ranged from 95 to 103%. The proposed method was applied for the arsenic speciation analysis of sediment pore-water samples, which were taken from the supernatant after centrifugation and filtration.